The Acute Subdural Hematoma (ASH) Score: A Grading Scale to Predict Postoperative Mortality. (16th November 2020) - Dincer, Alper; Stanton, Amanda N; Parham, Kevin; Carr, Matthew T; Opalak, Charles F; Valadka, Alex B; Broaddus, William C
Abstract: INTRODUCTION: Acute subdural hematomas (aSDH) are common, life-threatening injuries often requiring emergent surgery. Morbidity and mortality remain high despite prompt surgical evacuation. METHODS: The 2016 National Trauma Databank (NTDB) was queried to identify adult patients with an acute traumatic SDH who underwent craniectomy or craniotomy for evacuation within four hours of arrival to an emergency department. Multivariate logistic regression modeling identified risk factors independently associated with mortality. The ASH grading scale was developed based on a factor's strength and level of association with mortality. The model was validated using the 2017 NTDB dataset and the area under the receiver operating characteristics curve (AUC). RESULTS: A total of 2, 516 cases from the 2016 database met criteria for this study. The patients were 69.3% male with a mean age of 55.7 and overall mortality rate of 36.4%. Factors associated with mortality included age between 61–79 (OR = 2.3, P < . 001), age of 80 or older (OR = 6.3, P < . 001), loss of consciousness (OR = 2.3, P < . 001), GCS score of ≤8 (OR = 2.6, P < . 001), unilaterally (OR = 2.8, P < . 001) or bilaterally (OR = 3.9, P < . 001) unresponsive pupils, and midline shift >5 mm (OR = 1.7, P < . 001). Using these risk factors, the ASH score predicted progressively increasing risk of mortality ranging from 0% to 88% for scores ranging from 0 to 8, respectively (AUC = 0.74). For validation of the methodology, application of the ASH score to 3, 091 cases from 2017 resulted in similar accuracy for prediction of mortality (AUC = 0.75). CONCLUSION: The ASH score is a simple and validated grading scale that relies on easily accessible pre-operative factors to predict estimated mortality rates in patients with an aSDH who undergo surgical evacuation. The grading scale can be used by a wide range of health care professionals in the emergent clinical environment to guide management, aid clinical decision making, and counsel families.